A Prospective Investigation of Dietary Intake and Functional Impairments Among the Elderly. Issue 11 (27th July 2018) - Zhu, Jingjing; Xiang, Yong-Bing; Cai, Hui; Li, Honglan; Gao, Yu-Tang; Zheng, Wei; Shu, Xiao-Ou
Abstract: Limited information is available in Asian populations regarding the association of dietary intake and patterns with age-related functional impairments. Using data from 2 population-based cohort studies in China, the Shanghai Women's Health Study (1996–2015) and Shanghai Men's Health Study (2002–2015), we prospectively examined adherence to dietary guidelines, including the Chinese Food Pagoda, the Dietary Approaches to Stop Hypertension, and the Alternative Healthy Eating Index, as well as consumption of specific foods, for their associations with impairment in function, both physical (walking, hearing/vision) and mental (memory, decision-making). Included in the analyses were 30, 484 participants who had been followed for an average of 14.4 years and were between the ages of 70 and 86 years at the functional status assessment. Higher dietary-recommendation adherence scores were associated with a lower likelihood of developing functional impairments. The odds ratios ranged from 0.61 (95% confidence interval: 0.54, 0.70) to 0.83 (95% confidence interval: 0.72, 0.95) when extreme quintiles were compared. Higher fish, poultry, vegetable, and fruit intake, moderate red meat intake, and low rice consumption were associated with a reduced probability of having physical or mental impairments. Our findings highlight the importance of a high-quality diet in maintaining functional status among the aged population.